ChemInform Abstract: Relaxivity and Toxicological Properties of Manganese Oxide Nanoparticles for MRI Applications. Issue 27 (16th June 2016) - Hsu, Benedict You Wei; Kirby, Georgia; Tan, Aaron; Seifalian, Alexander M.; Li, Xu; Wang, John
Abstract: Review: 59 refs.